NIOBAT LITIУ KRISTALINING OРTIK XOSSALARI VA ULARNING GOLOGRAFIK INTERFEROMETRIADA QO‘LLANILISHI - Safarmatov Uchqun Sohibjon o‘g‘li, (TADQIQOTLAR, 2025)
Annotation From the presented curves, it is evident that the concentration coefficient has a significant impact on the short-circuit current value and, consequently, on the output power generated by the solar cell. However, as the concentration coefficient of solar radiation  increases,  the  absolute  rise  in  short-circuit  current  is  accompanied  by  a decrease in the fill factor of the current–voltage characteristic due to the enhanced recombination of minority charge carriers. As shown in Figure 2, the output electrical power exhibits a substantial increase up to a  concentration  factor of  Kₛ  = 80, after  which  saturation occurs,  and  further increases in the concentration coefficient result in only a minimal rise in generated power. A similar trend is observed in the dependence of the short-circuit current on Kₛ (Figure 1). Here as well, starting from Kₛ = 80, a decrease in the growth rate of Iₖ.ₓ. is observed; however, this change is less pronounced compared to the effect on output power.